Human capital and the adoption of information and communications technologies: Evidence from investment climate survey of Pakistan - Mazhar Mughal; Barassou Diawara (Kiel Institute for the World Economy (IfW), 2011)
This paper studies the impact of human capital on the adoption and diffusion of Information and Communications Technologies (ICT) in the Pakistani firms using the World Bank Enterprise Survey 2002-07. The paper considers various indicators of human capital and measures of ICT adoption and diffusion. On-the-job training, manager's level of qualification and production workers' level of education are found to positively determine the use of emails, website and other means of communication in a firm. The results are robust to the inclusion of geographical, sectoral and structural control variables. Firm size, sales and workers' compensation are also positively associated with the use of ICT. The findings show the importance of accumulation and development of human capital in the productivity growth in the era of skill-biased technical change. A concerted national effort for the enhancement of the workforce's computing skills is therefore a must if a developing economy such as Pakistan is to improve its competitiveness.
Keywords: I21; O10; 330; Human capital; education; ICT; Pakistan; Computergestütztes Verfahren; Unternehmen; Informationstechnik; Innovationsdiffusion; Humankapital; Bildungsniveau; Schätzung; Pakistan